Factores de riesgo asociados con anemia en niños de 6 - 36 meses del centro de salud Chacra colorada de Breña, julio - noviembre del 2021 - Bernal Mego, Juan Carlos (2022)
In this thesis entitled "Risk factors related to anemia in children aged 6 to 36 months at the Chacra Colorada de Breña Health Center, July to November 2021", the objective was: To determine the risk factors related to anemia in children aged 6 to 36 months at the Chacra Colorada de Breña Health Center. After carrying out the documentary analysis of the clinical histories of children between 6 and 36 months of age treated in said health center; it was found that: the age group of the children and exclusive breastfeeding are important factors that have to do with anemia in children. The conclusions reached in the present investigation allow us to establish that, in the age group of children under 1 year of age, the prevalence of anemia is present in 62.4% of them, and that exclusive breastfeeding is considered important and is practiced by 78.8% of the mothers of the children in question.